"Mutum": do murmúrio à letra (ou a experiência do cinema como expansão do campo literário): do murmúrio à letra (ou a experiência do cinema como expansão do campo literário) - Mírian Sousa Alves (2013)
This dissertation proposes a transposition from the theory of translation, as articulated by concrete poets, to the interface between literature and the cinema. Inthe course of the investigation of the relation between these two semiotic systems, this research notices that the encounter between literature and movies predates the emergence of narrative film and, therefore, it can be understood by means of alternative non-narrative perspectives. The investigation is built upon the analysisof the film Mutum (2007), by Sandra Kogut, which dialogues with the novel Campo geral (1956), by João Guimarães Rosa. Mutum actualizes Rosas text and, as a continuity of it, it allows the text to be reviewed through the realization of the film. As an eclipse, the films movement acts as a layer that, during a definite time, superimposes the literary text, giving it a new dimension: moving cuts of experience are added to the text. The analysis of the translating operation from Campo geral to Mutum points to the possibility of seeing cinematic experience as an expansion of literary space. Initially, the film Mutum is regarded here as a material transformation of Rosas novel. Afterwards, translation is regarded as a possibility of extension or continuity of the literary text. Finally, translation is seen as a process of subtraction or con-fusion. Curiously, the operation of subtracting the critical layers that coverthe text ultimately led the film to meet the writers poetry as a poetry of minus. Therefore, this dissertation starts with a perception of the film as a metamorphosis of the literary text and ends up by pointing to the filmic translation as a process that goes towards that which, despite all metamorphoses, keeps unchanged: the letter.